Love for All Hatred for None: Ajaran Teologis dan Respon Ahmadi terhadap Perusakan Masjid Miftahul Huda di Media Sosial - Muhammad Rizkita; Arfi Hidayat (Research Institute and Community Engagement of UIN MADURA, 2023)
As a result of their religious understanding that is considered different by the dominant group (mainstream), Ahmadiyah - especially those of the Qadian faith - are often the object of persecution in Indonesia with hatecrime nuances. Persecution involves collaboration between community organizations as civil society and the state, forming the phenomenon of godless nationalism. One form of persecution became the public spotlight due to the destruction of the Miftahul Huda mosque in Sintang Regency, West Kalimantan. Although the mosque attack ended on September 3, 2021, in fact, violence against the Indonesian Ahmadiyah Congregation (JAI) continued to occur afterwards. JAI was attacked through social media. This research method is qualitative with a virtual ethnography approach, which is further analyzed using social construction of technology (SCOT). This research tries to see how Ahmadiyah's religious doctrine responds to the violence they experience. And to what extent the teachings of Ahmadiyya's love of peace are realized in Ahmadi when responding to attacks after the destruction of the Miftahul Huda mosque, especially attacks that target JAI's official Instagram account, @ahmadiyah.id. The findings in this article show that the Ahmadiyya teachings have experienced persecution since their birth in India, and throughout the world. Facing this, Ahmadiyya responded with a religious doctrine of love and peace represented by the phrase love for all, hatred for none which is a form of interpretative flexibility in the review of social construction of technology. The response given by the Ahmadis looks passive and tends to be defensive, it is in accordance with their religious doctrine not to reply to anyone who hurts them. (Akibat pemahaman keagamaannya yang dianggap berbeda oleh kelompok dominan (mainstream), Ahmadiyah – khususnya yang beraliran Qadian – sering menjadi objek persekusi di Indonesia yang bernuansa kebencian (hatecrime). Persekusi melibatkan kolaborasi antara organisasi masyarakat sebagai civil society dengan negara membentuk fenomena nasionalisme bertuhan. Salah satu bentuk persekusi menjadi sorotan publik akibat peristiwa perusakan masjid Miftahul Huda di Kabupaten Sintang, Kalimantan Barat. Meski penyerangan masjid telah usai pada 3 September 2021, nyatanya kekerasan terhadap Jemaat Ahmadiyah Indonesia (JAI) terus terjadi setelahnya. JAI mendapat serangan lewat media sosial. Metode penelitian ini adalah kualitatif dengan pendekatan etnografi virtual, yang lebih lanjut dianalisis menggunakan social construction of technology (SCOT). Penelitian ini mencoba untuk melihat bagaimana doktrin keagamaan Ahmadiyah merespon kekerasan yang mereka alami. Dan sejauh apa ajaran cinta damai Ahmadiyah terealisasi dalam diri Ahmadi ketika merespon serangan pasca perusakan masjid Miftahul Huda khususnya serangan yang menyasar akun instagram resmi JAI yakni @ahmadiyah.id. Temuan dalam artikel ini memperlihatkan ajaran Ahmadiyah yang telah mengalami persekusi sejak awal kelahirannya di India, dan seluruh dunia. Menghadapi itu, Ahmadiyah membalasnya dengan doktrin keagamaan cinta damai yang diwakili dengan kalimat love for all, hatred for none yang merupakan bentuk dari interpretative flexibility dalam tinjauan social construction of technology. Respon yang diberikan oleh para Ahmadi terlihat pasif dan cenderung defensif, hal itu sesuai dengan doktrin keagamaan mereka untuk tidak membalas siapa saja yang menyakiti mereka.)